Prophetic rivalry, gender, and economics a study in revelation and Sibylline Oracles 4-5 - Stewart Lester, Olivia 1984-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2018)
Intro -- Preface -- Table of Contents -- Introduction: Prophets and Their Rivals -- A. The Texts -- I. Prophecy Across Religious and Canonical Boundaries -- II. Revelation, Sibylline Oracles 4-5, and Prophecy's Decline -- B. The Structure -- C. The Foci of This Study: Interpretation, Gender, and Economics -- I. Interpretation of Earlier Traditions -- 1. Interpretation for Prophetic Foundations and Prophetic Polemics -- 2. Interpretation and "Traditionary Processes" -- II. Gender -- 1. Gender and Prophetic Agency -- 2. Gender and Violence -- III. Economics -- 1. Prophetic Economies in Revelation and Sibylline Oracles 4-5 -- 2. The Economics of Prophecy and Prophecy's Reception -- D. Conclusion -- Chapter 1: Rival Prophets in Revelation: John, Balaam, and Jezebel -- A. Introduction -- B. John's True Prophecy -- I. Revelation as Prophecy -- II. John as a Prophet -- C. Balaam the Rival Prophet -- I. Balaam and Interpretation -- II. Balaam and Gender -- III. Balaam and Economics -- D. Jezebel, "Who Calls Herself a Prophetess" -- I. Jezebel and Interpretation -- II. Jezebel and Gender -- 1. Jezebel and Gender: A Close Reading of Revelation 2 -- 2. Jezebel and Gender within a Discourse of Divine Violence against Prophets -- 3. Jezebel, Babylon, and Sexual Violence against Women in Revelation -- 4. Jezebel and Gender: Conclusions -- III. Jezebel and Economics -- 1. Jezebel and Economics in 1-2 Kings -- 2. Jezebel and Economics in Revelation -- E. Conclusion -- Chapter 2: Balaam in Philo and Josephus -- A. Introduction -- B. Balaam in Philo -- I. Balaam in Philo: Interpretation -- II. Balaam in Philo: Gender -- III. Balaam in Philo: Economics -- IV. Balaam in Philo: Conclusion -- C. Balaam in Josephus -- I. Balaam in Josephus: Interpretation -- II. Balaam in Josephus: Gender -- III. Balaam in Josephus: Economics -- IV. Balaam in Josephus: Conclusion.
Description based on publisher supplied metadata and other sources
Keywords: Oracula Sibyllina; Bibel; Prophetie; Wirtschaft; Frühchristentum; Frühjudentum; Electronic books; Hochschulschrift